Concise Synthesis of Naphthalene-Based 14-Aza-12-Oxasteroids - Smriti Srivastava; Jun Luo; Daniel Whalen; Katherine N. Robertson; Amitabh Jha (Molecules)
A concise, transition metal-free four-step synthetic pathway has been developed for the synthesis of tetracyclic heterosteroidal compounds, 14-aza-12-oxasteroids, starting from readily available 2-naphthol analogues. After conversion of 2-naphthols to 2-naphthylamines by the Bucherer reaction, subsequent selective C-acetylation was achieved via the Sugasawa reaction and reduction of the acetyl group using borohydride, which resulted into the corresponding amino-alcohols. The naphthalene-based amino-alcohols underwent double dehydrations and double intramolecular cyclization with oxo-acids leading to one-pot formation of a C-N bond, a C-O bond and an amide bond in tandem, to generate two additional rings completing the steroidal framework. A series of 14-aza-12-oxasteroids were synthesized using our developed synthetic strategy in moderate yields, and the structure of one of the final products, 12a-Methyl-11-phenyl-11,12a-dihydro-1H-naphtho[2,1-d]pyrrolo[2,1-b][1,3]oxazin-3(2H)-one, was further confirmed by single crystal X-ray crystallography.